The Dynamics of Social Capital in Urban Communities in Facing Social Change in the Digital Era - Ahmad Mubarok (PT. AVID MEDIA INDONESIA, 2026)
This study aims to analyze the dynamics of social capital in urban communities in the face of social change triggered by the development of digital technology. The shift in social interaction patterns from relationships based on physical proximity to virtual connectivity has influenced the structure of social networks, trust-building mechanisms, and the validity of social norms in urban environments. A qualitative approach with a descriptive design was used to explore the meanings, experiences, and social practices of communities in utilizing digital spaces. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed thematically to identify patterns of social capital transformation. The results show that social capital has not experienced an absolute weakening, but rather has undergone a transformation in form and function. Social networks have become broader but tend to be fragmented, while social trust is more fluid and situational due to the mediation of digital technology. Social capital plays a crucial role as an adaptive resource that supports the ability of urban communities to respond to rapid social change. The sustainability of social cohesion is largely determined by the quality of social relations, digital literacy, and the role of communities and social institutions in managing social interactions. These findings confirm that strengthening social capital based on an adaptive and inclusive approach is a crucial strategy for the social resilience of urban communities in the digital era.